A Cross-Cultural Adaptation and psychometric validation of SISRI-24 among Malaysian Teachers - Ogunsola, Kazeem; Fontaine, Rodrique Ancelot Harvey; Jan, Mohammad Tahir (Advances in Social Sciences Research Journal, 2019)
The paper is aimed at validating the psychometric properties of SISRI-24 for effective performance among teachers in Malaysia. Through a list-based simple random sampling of 373 teachers, SISRI -24 was translated, adapted and validated. Using TCA procedure, experts validated the translated the instrument from both linguistic structure and semantic point of view. Its internal consistency was validated with Cronbach’s Alpha and CFA. EFA varimax normalized rotation extracted four components. Measure of internal consistency had Cronbach’s Alpha value of 0.911. CFA validated SISRI-19my with χ² / df ratio (354.512 / 141) = 2.514, RMSEA (0.077) and CFI (0.921) as reasonable spiritual intelligence fit model for Malaysian teachers. The adequacy of this paper’s findings is promising, suggesting that the Malaysian version of spiritual Intelligence self-Assessment Inventory scale would provide a valid instrument to develop spiritual intelligence among teachers. Practically, it would stimulate teaching interest irrespective of exigencies. Socially, it models spirited leaders whose role revolves on grooming younger generations towards nation building. Psychological, it acts as catalyst towards improved wellness. Theoretically, it contributes to body of knowledge on spirituality and organizational behaviour. Apart from the study being cross-sectional, it was limited only to private secondary school teachers. Future study may include other strata of teachers to improve SISRI-19my version. The study offers the first to empirically translate, adapt and validate a Malaysian version of SISRI-24.